WACANA BERITA POLITIK PILKADA KOTA PADANG PERIODE 2014-2019 DALAM MEDIA ONLINE PORTAL HARIAN SINGGALANG KAJIAN ANALISIS WACANA KRITIS PERSPEKTIF TEUN A. VAN DIJK - Nurassyiyah, Siti; Ermanto, Ermanto; Juita, Novia (Jurnal Bahasa dan Sastra, 2014)
The aim of this research is to explain the use of the tematic structure text and skematic structure text by the journalist in the political news of the second round period 2014-2019 of the mayor election in Padang in Singgalang daily news as the online media to expose the political power. The research is qualitative research. TheÂ  technique of data collection is using simak and catat technique. The analysis of the data is done by description of the analysis of Teun A. van Dijkâ€˜s perspectives. Based on the result of the research, it is concluded that the use of the structure of tematic text and the use of the structure of skematic text in the political news of the second round of mayor election of Padang in Singgalang online media, indicates that the political power exists. This phenomenon indicates that the media supports one of the candidate, Desri Ayunda-James Hellyward (Deje), so the news that is written is not neutral.